Finite-dimensional pointed Hopf algebras over finite 3 simple groups of Lie type V. Mixed classes in Chevalley 4 and Steinberg groups - Andruskiewitsch, Nicolas (2020)
We show that all classes that are neither semisimple nor unipotent in finite simple Chevalley or Steinberg groups different from PSLn(q) collapse (i.e. are never the support of a finite-dimensional Nichols algebra). As a consequence, we prove that the only finite-dimensional pointed Hopf algebra whose group of group-like elements is PSp2n(q) , PΩ4n+(q), PΩ4n-(q), 3D4(q) , E7(q) , E8(q) , F4(q) , or G2(q) with q even is the group algebra.